Synthesis of few novel benzo-1,5-substituted azepine derivatives fused to benzazepinone moiety through the corresponding oxoketene dithioacetal derivative (International Journal of Food and Nutritional Sciences, 2019)
The chemists in the field of drugs and pharmaceuticals have shown interest in benzo fused derivatives of azepinesand their analogues1-3.These compounds have extensive applications as anticonvulsants, antianxiety agents,analgesics, and sedatives.